A unified basis for design research and theory - Love, Terence (International Association of Societies of Design Research, 2005)
An epistemologically fundamental problem in design research is contradiction between two opposing perspectives: Belief that design research will lead to the activity of design being completely understood. Belief that research into design will ultimately be limited because design activity is dependent on human creativity and human creativity cannot be deterministically modelled in the manner of simple physical research.Both perspectives are strongly represented in the design literature. The contradiction between them has not been resolved, or addressed in an epistemologically conclusive manner.This paper addresses this problem by outlining a proposal for a unified basis for design theory that builds on previous research by the author in integrating social, environmental, ethical and technical factors in design theory. There are significant advantages for addressing this contradiction to reduce the widely acknowledged epistemological problems found in the design research literature. Addressing the issue also forms the basis for a unified theory of design. The proposal draws on: epistemology and theory of knowledge; ethology and evolutionary development; systems; and organisational theory. The use of ethology in this context is new in the field of design research. The paper concludes by outlining the benefits of the proposed unified basis for design theory and its limitations.